Enzymes Catalyzing Crotonyl-CoA Conversion to Acetoacetyl-CoA During the Autotrophic CO2 Fixation in Metallosphaera sedula - Liu, Li; Huber, Harald; Berg, Ivan A. (Frontiers in Microbiology, 2020)
Autotrophic Crenarchaeota use two different cycles for carbon dioxide fixation. Members of the Sulfolobales use the 3-hydroxypropionate/ 4-hydroxybutyrate cycle, whereas Desulfurococcales and Thermoproteales use the dicarboxylate/4-hydroxybutyrate cycle. While these two cycles differ in the carboxylation reactions resulting in the conversion of acetyl-CoA + 2 CO2 to succinyl-CoA, they have a common regeneration part in which succinyl-CoA is reconverted to two acetyl-CoA molecules. This common part includes crotonyl-CoA conversion to acetoacetyl-CoA, which has unequivocally been shown in Ignicoccus hospitalis (Desulfurococcales) and Pyrobaculum neutrophilus (Thermoproteales) to be catalyzed by a bifunctional crotonase/3-hydroxybutyryl-CoA dehydrogenase. It is a fusion protein consisting of an enoyl-CoA hydratase and a dehydrogenase domain. As the homologous bifunctional protein is present in Sulfolobales as well, its common functioning in the conversion of crotonyl-CoA to acetoacetyl-CoA was proposed. Here we show that a model autotrophic member of Sulfolobales, Metallosphaera sedula, possesses in addition to the bifunctional protein (Msed_0399) several separate genes coding for crotonyl-CoA hydratase and (S)-3-hydroxybutyryl-CoA dehydrogenase. Their genes were previously shown to be transcribed under autotrophic and mixotrophic conditions. The dehydrogenase Msed_1423 (and not the bifunctional protein Msed_0399) appears to be the main enzyme catalyzing the (S)-3-hydroxybutyryl-CoA dehydrogenase reaction. Homologs of this dehydrogenase are the only (S)-3-hydroxybutyryl-CoA dehydrogenases present in all autotrophic Sulfolobales, strengthening this conclusion. Two uncharacterized crotonase homologs present in M. sedula genome (Msed_0336 and Msed_0384) were heterologously produced and characterized. Both proteins were highly efficient crotonyl-CoA hydratases and may contribute (or be responsible) for the corresponding reaction in the 3-hydroxypropionate/ 4-hydroxybutyrate cycle in vivo.